Solution peculiarities of solving multiplication and division word problems - Martišius, Vaclovas; Balkutė, Živilė (Psichologija, 1999)
The main purpose of investigation was to evaluate the peculiarities of thinking of 9-11 years old children, when they are solving arithmetic word problems in mind without any opportunity to operate with visual aids. Problems of first two series were constructed analogical to the tasks by O. Frydman and P. Bryant. Solving word problems our children did not try to imagine or express in drawings the situation described in a problem, i. e. they solved differently than 5-6 years old children in the investigation of O. Frydman and P. Bryant. It is possible to make a conclusion that it is particularly difficult correctly to interpret the ratio of object quantity for 9-11 years old children. They are tending to relate this dimensionless ratio with amount of things. The common multiples of the two quantities have no influence on problem solving. Some children interpret multiplicative relations additively.